Screening of natural deep eutectic solvents for green synthesis of 2-methyl-3-substituted quinazolinones and microwave-assisted synthesis of 3-aryl quinazolinones in ethanol - Komar, Mario (Array, 2020)
In this study, two fast and efficient protocols for green synthesis of 3-substituted quinazolinones were perfomed. A synthesis of 2-methyl-3-substituted quinazolinones was performed in natural deep eutectic solvents, while 3-aryl quinazolinones were obtained by using microwave assisted synthesis. Benzoxazinone, which was used as an intermediate in the synthesis of 2-methyl-3-substituted quinazolinones, was prepared conventionally from anthranilic acid and acetic anhydride. In order to find the most appropriate synthetic path, twenty natural deep eutectic solvents were applied as a solvent in these syntheses. Choline chloride:urea (1 : 2) was found to be the most efficient solvent and was further used in the synthesis of 2-methyl quinazolinone derivatives (2–12). 3-Aryl quinazolinones (13–17), on the other hand, were synthesized in one-pot microwave-assisted reaction of anthranilic acid, different amines and trimethyl orthoformate. All compounds were synthesized in good to excellent yields, characterized by LC-MS/MS spectrometry and 1H- and 13C-NMR spectroscopy.